Circadian regulation of sleep in mammals. Issue 15 (June 2020) - Deboer, Tom
Abstract : Sleep is one of the many behaviours that is under the control of the circadian clock. Sleep is regulated by different brain regions, distributed over two major regulatory systems. The ascending reticular arousal system induces waking and alertness, whereas the ventrolateral preoptic area (VLPO) is thought to induce sleep. Consolidation of sleep and wake bouts are under control of the hypocretin releasing neurons in the lateral hypothalamus (LH). The mammalian circadian clock is located in the suprachiasmatic nucleus and regulates the alternation between the daily sleep/rest and waking/active period through the dorsomedial hypothalamus, which in turn activates the LH and supresses the VLPO, depending on time of day. The control that the circadian pacemaker has over sleep-wake regulation is limited. This loose coupling has become a threat in itself as the flexibility it allows in our 24/7 society is shown to make us prone to diseases like diabetes and cancer.